Mythological symbol of the ship in the novel “The history of the world in 10 ½ chapters” by J. Barnes - Керімова, Елізавета Ялчинівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Through a complex analysis, we examine the dynamics of the mythopoetic archetypes and symbols in the dystopian novel “The History of the World in 10½ Chapters” by Julian Barnes. We define that the main symbol of the novel is the ship. Using scientific papers on mythology by J. G. Frazer, J. Fawles and M. Makovsky we specify the main mythopoetic features of the ship videlicet: the citadel of death (death, floating coffin), salvation (hope of salvation), man (human civilization), church and art. By extensive review of the novel we characterize all of the peculiarities of the mythosymbol of the ship in “The History of the World in 10½ Chapters”. The one to be pointed out among them is that the most important features of the ship are two opposite and simultaneously interdependent mythosemantic functions of death and salvation. After thorough examination of the novel it becomes clear that with the help of this mythological symbol, the author sets the dynamics of the plot moving by chapters, as well as reveals the mythological picture of the world in the novel. In the odd’s chapters of the novel (“Guests", “Survivors” and “Upstream”), mythosymbol controls the development of the plot more clearly, while in the even ones, archetypal or syncretic comparisons, such as boat-mountain, boat-whale, boat-journey and the boat-church, which allows to understand deeper mythological picture of the world of the novel and the possibility of manifestation of the mythical character of the boat. The most important features are two opposite and simultaneously interdependent mososemantic functions: “death” and “salvation.